2022
DOI: 10.3389/fphys.2022.782592
|View full text |Cite
|
Sign up to set email alerts
|

A Lumped Two-Compartment Model for Simulation of Ventricular Pump and Tissue Mechanics in Ischemic Heart Disease

Abstract: Introduction: Computational modeling of cardiac mechanics and hemodynamics in ischemic heart disease (IHD) is important for a better understanding of the complex relations between ischemia-induced heterogeneity of myocardial tissue properties, regional tissue mechanics, and hemodynamic pump function. We validated and applied a lumped two-compartment modeling approach for IHD integrated into the CircAdapt model of the human heart and circulation.Methods: Ischemic contractile dysfunction was simulated by subdivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…Using a combination of echocardiography and sonomicrometry, Lyseggen et al showed that the viable LV myocardial pressure-strain curve switched from counter-clockwise to clockwise after 15 minutes of ischemia. The recent study by Koopsen et al15 reproduced similar plots using a two-compartment model of the ischemic ventricle and simulated the effects of reperfusion that parallel results reported by Lyseggen et al Our model framework, like Koopsen et al, illustrates…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Using a combination of echocardiography and sonomicrometry, Lyseggen et al showed that the viable LV myocardial pressure-strain curve switched from counter-clockwise to clockwise after 15 minutes of ischemia. The recent study by Koopsen et al15 reproduced similar plots using a two-compartment model of the ischemic ventricle and simulated the effects of reperfusion that parallel results reported by Lyseggen et al Our model framework, like Koopsen et al, illustrates…”
supporting
confidence: 80%
“…Witzenburg also accounted for compensatory changes in afterload parameters and showed that model predictions matched well with prior experimental (canine) studies. Koopsen et al 15 considered a similar, two compartment approach for simulating LV infarction; these authors included biventricular interaction and showed agreement with previously obtained canine data from Lyseggen et al 17 .…”
Section: Simulated Ischemiasupporting
confidence: 57%
See 2 more Smart Citations
“…These parameters are chosen because they are the most sensitive in determining ventricular strain patterns in patients with electromechanical dyssynchrony and myocardial infarction. The methodology to simulate virtual patients with myocardial infarction using a lumped two-compartment modeling approach integrated into the CircAdapt model is previously introduced in [17]. The resulting cohort is filtered with global hemodynamic parameter values and strain indices representative of a CRT cohort, found in literature, guidelines [18], and clinical data.…”
Section: A Circadapt Virtual Patient Datasetmentioning
confidence: 99%